Electronic communication convergence policy challenges in Asia - Hukill, Mark (Ed); Ono, Ryota (ED); Vallath, Chandrasekhar (ed) (New Delhi Sage, 2000)
The convergence of the telecommunications, information technology and broadcasting industries has been a subject of considerable policy discourse in recent years. These collection of essays examines the conceptual and practical challenges to electronic co
Keywords: Telecommunication-Mergers-Asia-Case studies; Computer industry-Mergers-Asia-Case studies; Electronic industries-Mergers-Asia-Case studies